Apakah Green Sukuk Menyebabkan Pengembalian Tidak Normal? - Luthfi Rahmawati Nur Hasanah (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2019)
Green sukuk must be appropriate with the stock criteria enforced by the principles of Islamic Jurisprudence (Sharia). Equity through three basic selections: sources of income, business activities, and financial factors to be recognized as Islamic stocks. However, the screening criteria can not apply universally especially to financial factors. Investor use financial ratios based on the book value of total assets or market value of the company to make a selection. This results criterion not only in different portofolio composition but also requires a variety of offsets and monitoring costs. The performance of 11 green sukuk from the JII main index using environmentally sharia screening criteria is analyzed in a multi-equation framework. Multi-equation framework have advantage of utilizing information from screening different criteria. These empirical findings indicate that differences in screening criteria do not significantly affect the green sukuk performance. If there is return that deviates from the risk of green sukuk. It is necessary to streamline quantitative screening criteria to avoid confusion among investing communities.